Ruptured functioning adrenal tumour, atypical presentation with renal colic and hypertension. Issue 12 (17th December 2020) - Elmoheen, Amr; Yousry, Mohamed; Elmesery, Ahmed; Bashir, Khalid
Abstract : Pheochromocytomas are uncommon tumours that originate in chromaffin cells. They are a representation of 0.1%–1% of all cases of secondary hypertension. Most pheochromocytomas are unilateral and benign, featuring catecholamine production, as well as the production of other neuropeptides. Pheochromocytomas are mostly located in the adrenal gland; the frequency of occurrence is highest between 30 and 50 years of age; however, up to 25% of cases may be linked to multiple endocrine neoplasia type 2, Von-Hippel-Landau disease and type 1 neurofibromatosis in the young. We present a case of ruptured left adrenal pheochromocytoma with an atypical presentation. A 30-year-old male patient presented with severe left flank pain and hypertension. The CT scan of the abdomen showed bleeding from the left adrenal mass, where resuscitation and angioembolisation were done. Embolisation of the inferior and superior arteries was done, but the middle failed. The patient experienced a significant drop in haemoglobin and a haemorrhagic shock post angioembolisation, which called for emergency laparotomy. The patient is currently doing well with an uneventful postoperative course.